INTEGRATION OF UNMANNED AERIAL VEHICLES FLYING BEYOND VISUAL LINE OF SIGHT INTO AIR TRAFFIC - Japins, Ivars; Kodors, Sergejs; Ežmale, Sandra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
In this article Author describes the potential of Unmanned aircraft systems (UAS) that are flying Beyond visual line of sight (BVLOS). There are countless commercial applications of BVLOS UAS. Author provides an insight of the main challenges that need to be addressed in order to make BVLOS UAS operations safe and to integrate them into air traffic.